HUBUNGAN RESILIENSI AKADEMIK DENGAN STRES AKADEMIK PADA MAHASISWA AKTIF BERORGANISASI BIMBINGAN DAN KONSELING UNIVERSITAS SRIWIJAYA - Nabila Ade Putri; Khadijah Lubis (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Academic stress is a significant issue among university students, especially those involved in organizational activities due to the dual burden of academic and organizational responsibilities. This study highlights the importance of academic resilience as an adaptive capability to cope with academic stress. Using a quantitative correlational approach, data were gathered through questionnaires distributed to 65 students of the Guidance and Counseling Study Program at Universitas Sriwijaya, selected using proportional stratified random sampling. The results of the Pearson correlation analysis revealed a significant negative relationship between academic resilience and academic stress. Students with higher resilience tend to experience lower levels of academic stress. These findings underline the crucial role of resilience-building in maintaining students’ mental health and academic success under dual pressures.